TRUANT EFFECT TOWARD FOR STUDENTS - Trinova, Zulvia; Hasanah, Yusratul; Nini, Nini (Al-Qalb : Jurnal Psikologi Islam, 2020)
The problems encountered in the field are still students who have truant behavior during class hours, do not attend school without information. This study describes the behavior of students who frequent truancy, the factors that cause truancy, the role of guidance and counseling teachers in overcoming truancy. Qualitative descriptive research method with the type of research field research. The data sources come from guidance and counseling teachers, subject teachers, and students. Data were collected through observation, interviews, and documentation. The results of this study are: (1) the forms of behavior of students who often skip truancy in various ways, such as without permission, asking for permission to leave by pretending to be sick and often leaving during class hours, (2) the cause of truant students is influenced by factors internal and external. Internal factors, students are lazy in learning and prefer to watch YouTube and play games, lazy with subject teachers who are often angry, and bored of being in class and because they have not completed assignments or homework. External factors are the existence of calls from peers, (3) the role of guidance and counseling teachers in overcoming truancy behavior of students is to direct, guide students to be better.